František Udržal a agrární studenstvo - Charbuský, Miloš (Univerzita Pardubice, 2000)
Prospective Defence Minister and Prime Minister of the Czechoslovak Republic Mr. František Udržal entered the Agrarian Party in 1906. The main cause for this was to retain the favour of village voters. Many year's support of the Habsburg Dynasty during the First World War unabled hem immediately after formation of Czechoslovakia in 1918 to become one of its leaders. To come back he used the endavour of agrarian academics to create a united organization. He participated in its creation and in 1922 he even became the president of the Agrarian Party which had strenghtened his position within the party.
Keywords: politici; Udržal, F.; agrární strana; Rakousko-Uhersko; Československo; politický vývoj; dějiny